Educação ambiental nos anos iniciais: a construção de uma proposta curricular com abordagem ciências-tecnologia-sociedade-ambiente - Souza, Dolores Albino de (2018)
The concern with the environment is a current worldwide issue, and the Environmental Education is a path to try and reverse the rational values of the contemporary society. This research aims to analyze the development of a science proposal accordingto the Environmental Education according to ascientific, technological, social and environmental approach, performed with 5th grade students of the PedroII a public federal school. The research background was an environmental problem stemming from how modern society produces and consumes, which demands critical and reflective action on events, values and people's behavior, showing social, economic and political relations affected by the environmental situation. A didactic sequence which targets elementary school teachers was organized as educational product. This product aimed to make teachers and students aware of the development of activities in Environmental Education which show not only environmental problems, but also the socioeconomic and cultural ones that environmental happenings encompass. An open survey with the teachers involved was conducted at the end of the sequence to prove the product validity. Through a qualitative analysis of the teachers' answers and assessment of the students' performance, it was possible to check that the use of the didactic sequence had a positive impact, helping the students to develop axiological, ethical and critical aspects, besides the motivation to learn.